Gc Subtypes Demonstrated by Isoelectric Focusing: Further Data and Description of New Variants among an African Sample (Fula) from Senegal - (:unkn) unknown (My University, 1978)
The polymorphism of the Group Specific Component (Gc) was studied in serum samples from a Fula population of Senegal (Western Africa) using isoelectric focusing in slab polyacrylamide gel followed by immunofixation. The isoelectric focusing patterns of various Gc phenotypes were compared to the patterns obtained by polyacrylamide disc electrophoresis. Besides the two subtypes,Gc1F andGc1S ofGc1 and theGcAb gene, aGc1 variant and aGc2 variant were discovered and namedGc1b andGc2b respectively. The results were compared to the data obtained in a Pygmy population. They confirmed the high degree of polymorphism of the Gc protein in African populations.
Keywords: African Research